PEMANFAATAN MODEL PEMELAJARAN MIND MAPING PADA MATA KULIAH BAHASA INGGRIS - Jenita Anjani Br Sembiring; Nadia Hagana Bangun (Universitas Quality, 2023)
The teaching and learning process is a process where there is two-way communication with the aim that the learning material delivered can be well received. In this process as an educator, it is appropriate to try to find and use various ways so that the material being taught can be well understood by students. The mind mapping learning model is an effective way to use in English courses, especially at the undergraduate level of applied environmental health POLTEKES KEMENKES Kabanjahe third semester. Based on the results of the survey analysis in the field, the use of the mind mapping learning model made a very positive contribution. There are also benefits, including first, it is very useful in learning, especially in English courses. It can be seen from 62 respondents 100% agree that this learning model is very useful for English courses. Second, increasing student concentration in the teaching and learning process, it can be seen from 62 respondents 92.6% agreed that their concentration increased by using this model. Third, it can increase student imagination, 93% agree on this. And fourth, it can make the learning atmosphere more interactive. It can be seen from 62 respondents, 88.7% of them agree that the mind mapping learning model can liven up the learning atmosphere.Keywords: Learning mode; Mind mapping; English.